Bank Market Power and Loan Contracts: Empirical Evidence. (12th June 2017) - Hasan, Iftekhar; Liu, Liuling; Wang, Haizhi; Zhen, Xinting
Abstract : Using a sample of syndicated loan facilities granted to US corporate borrowers from 1987 to 2013, we directly gauge the lead banks' market power, and test its effects on both price and non‐price terms in loan contracts. We find that bank market power is positively correlated with loan spreads, and the positive relation holds for both non‐relationship loans and relationship loans. In particular, we report that, for relationship loans, lending banks charge lower loan price for borrowing firms with lower switching cost. We further employ a framework accommodating the joint determination of loan contractual terms, and document that the lead banks' market power is positively correlated with collateral and negatively correlated with loan maturity. In addition, we report a significant and negative relationship between banking power and the number of covenants in loan contracts, and the negative relationship is stronger for relationship loans.